Animal kingdom. The complete third season [videorecording (DVD)] - Lisco, Jonathan (Warner Bros. Home Entertainment, 2019)
The Codys are back, and the ties that bind them are about to be stretched to the limit in the third season of this bold, adrenaline-fueled hit drama about a Southern California crime family. Cody clan matriarch Janine "Smurf" Cody, takes in estranged grandson Joshua 'J' Cody following his mother's overdose on heroin. In last season's shocking conclusion, second-in-command Baz was shot while on his way to Mexico after framing Smurf for murder.